Resepsi Video ‘Manisan Belimbing Wuluh Disulap Jadi Kurma' di YouTube 'Dish is Gan' - Samuel Hady Gandojo; Rudy Harjanto; Yunita Sari (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
Culinary content using local ingredients has gained popularity on digital platforms, reshaping how audiences respond to culinary innovations using local ingredients. This study aims to share how viewers perceive the cooking video